Surgical exposure and orthodontic traction of impacted maxillary central incisor after alteration of eruption sequence: A case report - Gabriela Leite Pedroso; Gustavo Lopes Puls; Ana Paula Valladares De Almeida; Fabiana Cardoso Pereira Valera; Fábio Lourenço Romano (Contemporary Pediatric Dentistry)
Delayed diagnosis of tooth eruption disturbances may result in the impaction of permanent teeth. This case report describes the clinical management of an impacted maxillary permanent central incisor in an 8-year-old boy with good general health, skeletal Class I relationship (ANB = 2°), posterior crossbite, and transverse maxillary deficiency. The patient underwent rapid palatal expansion, followed by orthodontic traction of the impacted incisor. Eruption was achieved within six months, and by the end of the mixed dentition stage, the patient exhibited a stable occlusion with successful alignment of the incisor. This case highlights the importance of early orthodontic assessment and continuous follow-up from the primary to permanent dentition. Timely diagnosis and treatment planning during growth can facilitate favorable outcomes and reduce the risk of future occlusal complications.